Optimization of Non‐Pyrolyzed Lignin Electrodes for Sustainable Batteries. (7th December 2022) - Ail, Ujwala; Nilsson, Jakob; Jansson, Mattias; Buyanova, Irina A.; Wu, Zhixing; Björk, Emma; Berggren, Magnus; Crispin, Xavier
Abstract: Lignin, a byproduct from the pulp industry, is one of the redox active biopolymers being investigated as a component in the electrodes for sustainable energy storage applications. Due to its insulating nature, it needs to be combined with a conductor such as carbon or conducting polymer for efficient charge storage. Herein, the lignin/carbon composite electrodes manufactured via mechanical milling (ball milling) are reported. The composite formation, correlation between performance and morphology is studied by comparison with manual mixing and jet milling. Superior charge storage capacity with ≈70% of the total contribution from the Faradaic process involving the redox functionality of lignin is observed in a mechanically milled composite. In comparison, manual mix shows only ≈30% from the lignin storage participation while the rest is due to the electric double layer at the carbon–electrolyte interface. The significant participation of lignin in the ball milled composite is attributed to the homogeneous, intimate mixing of the carbon and the lignin leading the electronic carrier transported in the carbon phase to reach most of the redox group of lignin. A maximum capacity of 49 mAh g −1 is obtained at charge/discharge rate of 0.25 A g −1 for the sample milled for 60 min. Abstract : Here, the role of mixing methods to form lignin/carbon composite is reported and the interplay between the morphology and the electrochemical property is investigated. Three methods of mixing are studied, namely manual mixing, jet milling, and ball milling and their effect on charge storage capacity are discussed.